1986
DOI: 10.1111/j.1440-1754.1986.tb00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A status in children who are prone to respiratory tract infections

Abstract: The effect of Vitamin A supplementation on susceptibility to acute respiratory infections was investigated in a randomized controlled trial. One hundred and forty-seven preschool-age children with a history of frequent respiratory illness were randomized into Vitamin A supplemented (450 pg/day) and placebo groups. Respiratory symptoms were recorded on a daily basis over a period of 11 months. The children who received the supplement experienced 19% fewer episodes of respiratory symptomatology (Pt0.05) than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In fact, some of the hospital-based studies suggest an apparent increase in indicators of severity associated with vitamin A supplementation (41,85,105,146). A number of community-based trials have also found an apparent increase in respiratory symptoms in relation to vitamin A supplementation (34,39,103,104,112,136,144), particularly among children who are not undernourished. It is not clear whether this apparent increase in respiratory symptoms may be due to a proinflammatory immune response associated with the supplements.…”
Section: Vitamin a Supplementation And Clinical Outcomesmentioning
confidence: 96%
“…In fact, some of the hospital-based studies suggest an apparent increase in indicators of severity associated with vitamin A supplementation (41,85,105,146). A number of community-based trials have also found an apparent increase in respiratory symptoms in relation to vitamin A supplementation (34,39,103,104,112,136,144), particularly among children who are not undernourished. It is not clear whether this apparent increase in respiratory symptoms may be due to a proinflammatory immune response associated with the supplements.…”
Section: Vitamin a Supplementation And Clinical Outcomesmentioning
confidence: 96%
“…A recent study (Sempertegui et al 1999) reported that vitamin A (3 mg retinol equivalents per week for 40 weeks) decreased the incidence of lower respiratory tract infections in underweight children compared with placebo treatment, but increased the incidence in normal-weight children. Supplementation of Australian children with a history of respiratory infections caused a reduction in rate of lower respiratory disease of 25 % (Pinnock et al 1986). Shenai et al (1987) reported reduced incidence of bronchopulmonary dysplasia in vitamin A-de®cient low birth weight infants given vitamin A.…”
Section: Vitamin Amentioning
confidence: 99%
“…Vitamin A plays a substantial role, especially in the respiratory epithelium and the lung. During moderate vitamin A deficiency, the incidence of diseases of the respiratory tract is considerably increased and repeated respiratory infections can be influenced therapeutically by a moderate vitamin A supplementation (Pinnock et al, 1986a;Sommer, 1993;West et al, 1991). In addition to the importance of the vitamin for lung function, vitamin A is also responsible for the development of many tissues and cells as well as for the embryonic lung development.…”
Section: Protecting Factorsmentioning
confidence: 99%
“…With reduced retinol plasma levels repeated infections are more often described (Barreto et al, 1994;Filteau et al, 1993;Pinnock et al, 1986b) and they are counted among the main complications of a poor vitamin A supply in developing countries. In addition, the serum vitamin A level during infectious diseases, particularly of the respiratory tract, continues to drop (Neuzil et al, 1994).…”
Section: Protecting Factorsmentioning
confidence: 99%